Knowledge levels for the prevention of gout arthritis in the elderly - Aisyah Salsabila Nur’Azizah; Kartinah Kartinah (Malahayati International Journal of Nursing and Health Science, 2025)
Background: The elderly state will be faced by every human and will develop into a more diverse issue as life expectancy is expected to exceed 70 years. Consequently, the population of elderly individuals in Indonesia is likely to surpass that of young children. As people age, they become increasingly vulnerable to diseases, one of which is gout arthritis. Gout arthritis is a condition caused by the accumulation of monosodium urate crystals in the body, resulting from hyperuricemia, which is characterized by elevated levels of uric acid due to disorders in purine metabolism. This condition is marked by joint pain, which disrupts the daily activities of those affected. Purines naturally exist in the body and are found in all foods, whether from animal sources like meat and organ meats or plant sources such as vegetables, fruits, and legumes. There are foods with both high and low purine content. Purpose: To analyze the relationship between knowledge level and efforts to prevent gout arthritis in the elderly. Method: A cross sectional approach (relationship and association), the population in this study is the elderly who have gout arthritis at the Grogol Health Center from January to February 2024 which is 150 people. The number of samples used was 60 people who came to the Grogol Health Center with Gout Arthritis and were given a questionnaire sheet. Results: In the study, it can be assumed that the behavior of the elderly in preventing Gout Arthritis is good if the elderly's knowledge about Gout Arthritis is good, because knowledge has a great influence on the behavior of the elderly about Gout Arthritis. With the results of the analysis using the Chi Square Test, a p-value of 0.012 (α<0.05) was obtained, which means that there is a relationship between the level of knowledge and efforts to prevent Gout Arthritis in the elderly. Conclusion: There is a relationship between the level of knowledge and efforts to prevent Gout Arthritis in the elderly. Good knowledge about Gout Arthritis is the main capital for preventing gout arthritis in the elderly. Suggestion: The nurses are expected to be able to provide socialization, counseling and health education related to Gout Arthritis to the elderly so that the elderly can understand how to prevent Gout Arthritis.